Promoting adolescent reproductive health: role of NGOS, parental care & sex education (1997)
Reproductive health care seeks to meet in male and female adolescents, the health needs assocaited with sexuality. This paper in taking a look at the reproductive health of adolescents, outlined the very positive roles the NGOs, parents and the school can play through appropriate sex education. The paper started off by giving seven reasons why the reproductive health of adolescents in Nigeria must be promoted. The paper reviewed the major UN conferences that have bearing with adolescents reproductive health and proffered actions that can be taken to achieve a number of strategic objectives based on the plans of action. On the role of NGOS, the paper advocated that NGOs which are strong forces to be reckoned with in the area of programme development and promotion of adolescent reproductive health, should retain the gains of the past and stregthen the weakness of the present, in the area of promotion of adolescent reproductive health. Since parental care is sine-qua-non to every aspect of the adolescent's life, reproductive health inclusive, parents were implored to ensure that practices , which will not promoted adolescents reproductive health, be reduced if not eliminated. Sex education should be seen as a whole area of interpersonal relations affecting human sexuality, and not just as a course emphasing soley the devices and methods of preventing pregnancies or avoiding STDs and STIs. This view of sex education will make adolescents in and out of school benefit from sex education. The paper concludes on the note that everybody should come together to nurture adolescents and promote their reproductive health